2021
DOI: 10.1111/clr.13682
|View full text |Cite
|
Sign up to set email alerts
|

Crestal bone loss associated with different implant surfaces in the posterior mandible in patients with a history of periodontitis. A retrospective study

Abstract: ObjectiveTo retrospectively assess the interproximal bone loss (CBL) in external hexagon implants (EHI), with different surface micro‐topography, placed in the posterior mandible in patients with a history of periodontitis undergoing supportive periodontal care.Material and methods268 consecutive patients received 755 EHI implants in the mandibular molar region between 2007 and 2015 with the following surface characteristics: 72 turned, 145 hybrids (double acid‐etched/turned), and 538 anodized. CBL was yearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Another important factor that may explain the heterogeneous results reported in the literature comparing marginal bone level changes between implants with different surface microtopographies may be related to the different sample populations used in the different studies. In this study, we purposely selected patients with history of periodontitis, since these patients have shown significant higher bone loss when comparing anodized surface implants to hybrid and turned implants (Sicilia et al, 2021). Similarly, these patients have shown a higher incidence and progression of peri-implantitis, when comparing rough surface with machined surface implants (Hanisch et al, 1997;Esposito et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor that may explain the heterogeneous results reported in the literature comparing marginal bone level changes between implants with different surface microtopographies may be related to the different sample populations used in the different studies. In this study, we purposely selected patients with history of periodontitis, since these patients have shown significant higher bone loss when comparing anodized surface implants to hybrid and turned implants (Sicilia et al, 2021). Similarly, these patients have shown a higher incidence and progression of peri-implantitis, when comparing rough surface with machined surface implants (Hanisch et al, 1997;Esposito et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To prevent biologic complications because of the exposure of the rough surface secondary to bone loss, the use of one-piece implant designs (such as tissue level implants), hybrid implant surfaces, and the subcrestal placement of implants have been proposed. [150][151][152][153][154][155] To minimize the initial bone remodeling associated with vertical ridge augmentation procedures, a second protecting layer of bone grafting at the time of implant placement has also been advocated. 146 Results using a mixture of a slowly resorbable xenogenic bone graft and autogenous bone chips covered with a resorbable membrane demonstrated that epi-crestally placed implants into vertically augmented bone exhibited excellent marginal bone stability.…”
Section: Long -Term Outcome S Of Vertic Al Ridg E Aug Mentation Proce...mentioning
confidence: 99%
“…In this context, implant design and surface characteristics may play a role. To prevent biologic complications because of the exposure of the rough surface secondary to bone loss, the use of one‐piece implant designs (such as tissue level implants), hybrid implant surfaces, and the subcrestal placement of implants have been proposed 150–155 …”
Section: Long‐term Outcomes Of Vertical Ridge Augmentation Proceduresmentioning
confidence: 99%